Expression of Selenoprotein Genes and Association with Selenium Status in Colorectal Adenoma and Colorectal Cancer - Hughes, David J; Kunická, Tereza; Schomburg, Lutz; Liška, Václav; Swan, Niall; Souček, Pavel (Nutrients, 2018)
Dietary selenium (Se) intake is essential for synthesizing selenoproteins that are important in countering oxidative and inflammatory processes linked to colorectal carcinogenesis. However, there is limited knowledge on the selenoprotein expression in colorectal adenoma (CRA) and colorectal cancer (CRC) patients, or the interaction with Se status levels. We studied the expression of seventeen Se pathway genes (including fifteen of the twenty-five human selenoproteins) in RNA extracted from disease-normal colorectal tissue pairs, in the discovery phase of sixty-two CRA/CRC patients from Ireland and a validation cohort of a hundred and five CRC patients from the Czech Republic. Differences in transcript levels between the disease and paired control mucosa were assessed by the Mann-Whitney U-test. GPX2 and TXNRD3 showed a higher expression and GPX3, SELENOP, SELENOS, and SEPHS2 exhibited a lower expression in the disease tissue from adenomas and both cancer groups (p-values from 0.023 to <0.001). In the Czech cohort, up-regulation of GPX1, SELENOH, and SOD2 and down-regulation of SELENBP1, SELENON, and SELENOK (p-values 0.036 to <0.001) was also observed. We further examined the correlation of gene expression with serum Se status (assessed by Se and selenoprotein P, SELENOP) in the Irish patients. While there were no significant correlations with both Se status markers, SELENOF, SELENOK, and TXNRD1 tumor tissue expression positively correlated with Se, while TXNRD2 and TXNRD3 negatively correlated with SELENOP. In an analysis restricted to the larger Czech CRC patient cohort, Cox regression showed no major association of transcript levels with patient survival, except for an association of higher SELENOF gene expression with both a lower disease-free and overall survival. Several selenoproteins were differentially expressed in the disease tissue compared to the normal tissue of both CRA and CRC patients. Altered selenoprotein expression may serve as a marker of functional Se status and colorectal adenoma to cancer progression.
Keywords: selenoprotein P; lidé; Middle Aged; Gene Expression Regulation; Selenium; Genetic Markers; glutathionperoxidasa; Female; genetické markery; Thioredoxin Reductase 1; Ireland; Humans; Irsko; Adenoma; Glutathione Peroxidase; Česká republika; selen; lidé středního věku; kohortové studie; thioredoxinreduktasa 1; Cohort Studies; mužské pohlaví; Selenoproteins; kolorektální nádory; Czech Republic; ženské pohlaví; Selenoprotein P; Proportional Hazards Models; thioredoxin-disulfidreduktasa; Aged, 80 and over; Colorectal Neoplasms; Thioredoxin-Disulfide Reductase; proporcionální rizikové modely; senioři nad 80 let; Male; Aged; adenom; regulace genové exprese; selenoproteiny; senioři